Speciality of decision making choice in retail market of finance services - Sūdžius, Vytautas (Business: Theory and Practice, 2007)
The complicated client behaviour, especially during the decision-making process, causes problems to business specialists working in finance sector. That makes one to look for a theoretical basis and carry out surveys in order to explain the factors influencing the client when making a decision about buying finance services. The objective of this research is to identify possible applications of factors and their interaction. In order to achieve the set target, the following tasks had to be solved: to analyse the main concepts about client’s decision-making process in finance sector; overview and systematize factors and make new classification; to create theoretical model identifying all key factors, taking into consideration specific Lithuanian finance market features and local environmental, economical and social circumstances; to estimate and analyze the output results in order to indicate possible applications of the above mentioned factors. This research indicates the main factors and groups of factors influencing decision making of clients: different value and features of various finance services, role of internal and external marketing complex and situational factors. Results of survey also let us identify means how to improve finance services and the methods they are provided to retail market.Article in Lithuanian.Apsisprendimo naudotis finansinėmis paslaugomis mažmeninėje rinkoje ypatumaiSantrauka. Komplikuota klientų elgsena, pasirenkant finansines paslaugas, kelia verslui ir finansų rinkoms problemų. Būtinos tam tikros prielaidos ir teorinė bazė, leidžianti nustatyti klientų bruožus ir veiksnius, galinčius paaiškinti finansinių paslaugų pasirinkimą. Darbo tikslas - nustatyti ir įvertinti aplinkos veiksnių poveikį klientų sprendimams, pasirenkant finansines paslaugas. Išanalizuotos pagrindinės klientų finansinių paslaugų pasirinkimą aiškinančios koncepcijos, peržiūrėti ir susisteminti veiksniai, veikiantys apsisprendimą bei parengtas teorinis modelis. Tiriant aplinką ir veiksnius, išryškėjo ypatinga jų sąsaja su finansinių paslaugų verte ir specifika, kurie ir nulemia poveikį priimamiems sprendimams. Apibendrinta tyrimų medžiaga, analizuojanti, kaip finansų įstaigos turėtų rengti paslaugų politiką, atsižvelgiant ne tik į veiksnių grupes, bet ir į finansų įstaigų ir klientų palaikomų ryšių pobūdį, paslaugų vertę, užimamą poziciją rinkoje.Reikšminiai žodžiai: apsisprendimas, finansinės paslaugos, klientas, modelis, rinka, vertė.